PROFIL KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI SELF EFFICACY (EFIKASI DIRI) SISWA TERHADAP MATERI PERSAMAAN LINGKARAN DI SMA NEGERI 13 BONE - Arifin, Sartika; Trisno, Andi Trisno; Iswandi, Iswandi; Arifin, Sadriwanti (FKIP Universitas Mataram, 2024)
This research is a qualitative research with a descriptive approach which aims to determine Mathematical Reasoning Ability in terms of students' Self efficacy regarding Circle Equation Material at SMA Negeri 13 Bone class XII MIPA. The data processed is the result of interviews with 1 (one) student who has high self-efficacy, 1 (one) student who has moderate self-efficacy, 1 (one) student who has low self-efficacy. The data collection methods used were observation, interviews, and mathematical reasoning ability tests. The results of this study show that students' Self efficacy influences the Mathematical Reasoning ability of students at SMA Negeri 13 Bone. Based on the interview results, subjects who have high self-efficacy can complete five of the five indicators of mathematical reasoning ability, subjects who have moderate self-efficacy can complete three of the five indicators of mathematical reasoning ability, subjects who have low self-efficacy can complete two of the five indicators of reasoning ability mathematics, which means that the better the students' self-efficacy, the better their mathematical reasoning abilities will be.